Post-dexamethasone Cortisol, Self-inflicted Injury, and Suicidal Ideation among Depressed Adolescent Girls - Beauchaine, Theodore P. (J Abnorm Child Psychol, 2015)
Although the dexamethasone suppression test (DST) has limited use as a marker of depression given inadequate sensitivity and specificity, it marks prospective risk for suicide among adults. However, few studies have examined associations between the DST, suicidal ideation, and self-inflicted injury (SII) among adolescents, even though SII is the single best predictor of eventual suicide. We evaluated the DST as a correlate of suicidal ideation and retrospective reports of self-inflicted injury (SII) among adolescent girls, ages 13–17, with histories of depression (n=28) or depression/self-harm (n=29). Lower post-DST cortisol was associated with suicidal ideation and SII, over-and-above parent-reports and combined parent-/self-reports of internalizing and externalizing behavior. These findings are consistent with recent acquired capacity models of stress-related psychopathology in which hypothalamic-pituitary adrenal (HPA) axis function is altered through epigenetic/allostatic mechanisms among vulnerable individuals who incur adversity early in life.